Semi-infinite moving crack in an orthotropic strip sandwiched between two identical half planes - Singh A.; Das S.; Altenbach H.; Craciun E.-M. (My University, 2025)
The problem of semi-infinite moving crack situated in a strip of a linear elastic orthotropic material sandwiched between two identical half planes has been considered. The assumed boundary value problem has been solved to convert it into the standard Wiener-Hopf equation by using Fourier transform technique. Further the Wiener-Hopf equation has been solved to obtain analytical expression for stress intensity factor and crack opening displacement at the tip of the crack for plane stress and plane strain cases. The effects of elastic material constants and propagation of the crack tip on stress intensity factor and crack opening displacement at the tip of crack have been displayed graphically for various particular cases for a combination of orthotropic materials. © 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim